Improving Self-Esteem In Breast Cancer Survivors Through A Monopoly Game Named Bermain Asik Mengenal Diri (Bersinar) - Maulida, Mutia Nadra; Rahmawati, Fuji; Cahya, Bernica Indah (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: Psychological problems experienced by breast cancer patients have a negative impact that can worsen their quality of life. Self-esteem is one of the psychological problems in breast cancer patients. Low self-esteem can have a negative impact on incomplete breast cancer treatment. One of the efforts to increase self-esteem is through game simulation using the monopoly named Bermain Asik Mengenal Diri (BERSINAR) (Eng: fun play to know yourself).Objective: This study aims to determine the increase in self-esteem in breast cancer patients through the Monopoly named Bermain Asik Mengenal Diri (Bersinar).Methods: The research design used pre-experimental with a one-group pretest-posttest design without a control group to measure the increase in self-esteem in breast cancer patients through the monopoly named Bermain Asik Mengenal Diri (Bersinar). The research respondents were 26 people. The sampling technique was Total Sampling. Data analysis used Marginal Homogeneity.Results: The results of the marginal homogeneity statistical test showed a p-value of 0.000  ≤ 0.05 that there is a significant difference in self-esteem before and after being given an intervention through the monopoly named Bermain Asik Mengenal Diri (BERSINAR).Conclusion: The monopoly named Bermain Asik Mengenal Diri (BERSINAR) had a positive impact on increasing self-esteem in breast cancer patients. It can be concluded that the game Monopoly Bermain Asik Mengenal Diri (BERSINAR) can improve self-esteem in breast cancer patients.